Deep‐Red Luminescent Molybdenum(0) Complexes with Bi‐ and Tridentate Isocyanide Chelate Ligands. Issue 8 (12th May 2022) - Herr, Patrick; Schwab, Alexander; Kupfer, Stephan; Wenger, Oliver S.
Abstract: In octahedral complexes, molybdenum(0) has the same 4d 6 valence electron configuration as ruthenium(II), which is beneficial for establishing energetically low‐lying metal‐to‐ligand charge transfer (MLCT) excited states. Those MLCT states often show luminescence, and they can furthermore undergo photoinduced electron and energy transfer reactions that are of interest in the context of solar energy conversion, sensing, or photocatalysis. Molybdenum is roughly 100 times more abundant than ruthenium, and it seems desirable to increase our fundamental understanding of the photophysical properties of complexes made from non‐precious metals. We report here on the luminescence behavior of two new homoleptic molybdenum(0) isocyanide complexes, one with three bidentate, the other with two tridentate chelate ligands. The key novelty is the incorporation of thiophene units into the ligand backbones, causing strongly red‐shifted photoluminescence with respect to comparable molybdenum(0) isocyanides with phenylene units in the ligand backbones. Combined experimental and computational studies provide detailed insight into the photophysical properties of this compound class. This work is relevant for the development of new luminescent compounds with possible applications in lighting and sensing, and it complements current research efforts on photoactive complexes with other abundant transition metal and main group elements. Abstract : Seeing red : Tris(bidentate) and bis(tridentate) arylisocyanide coordination environments lead to deep‐red‐emitting molybdenum(0) compounds with photophysical properties resembling those of osmium(II) polypyridine complexes.